Investigating Students’ Verbal Competencies in Relation to Their Personality Traits - HS, Nurianti; Nurwahyuningsih, Pebrina; Erna, Nana (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Oral Communication is a crucial skill, particularly in higher education, where students must engage and articulate concepts effectively. Nonetheless, speaking proficiency can be affected by other factors, one of them is personal traits. This study seeks to examine the speaking ability of students in relation to their personality types. According to the Big Five Personality’ Theory, people are classified into personality types such as extrovert, conscientiousness, openness, agreeableness, and neuroticism which influence how they communicate verbally. To determine the relationship between the two variables, this study conducted a qualitative method involving questionnaires, students’ speaking ability test, and interview. The findings surprisingly showed that extroverted personality turned out to have small contribution to speaking ability. This trait did not have a strong correlation with speaking skill seems contradictory because extroverts are often perceived as more communicative. On other hand, openness trait has the highest impact in communication. This type likely to participate more comfortably in discussion and construct logical arguments fluently in English. Although students with openness have fewer opportunities to talk than extrovert, their speaking components such as pronunciation and word usage were extremely accurate.